L’invenzione del consenso: il caso della lingua franca / Inventing consensus: the case of the lingua franca - Venier, Federica (Rivista Italiana di Filosofia del Linguaggio)
This article illustrates a double operation of ideological construction of an inexistent consensus, exemplified by the case of the lingua franca, a simplified variant of Italian. The analysis of the simplification processes which drew to the lingua franca and of the glottonyms which were employed to designate this linguistic reality will show how far its reality is from that of an irenic non-lieu